Tax Planning or Profit Shifting? Investigating the Drivers of Transfer Pricing in Indonesia's Pharmaceutical Sector - Sarini, Anggun; Muhammad, Rifqi (Economics, Business, Accounting & Society Review, 2025)
This study investigates the firm-level determinants of transfer pricing practices within Indonesia’s pharmaceutical sector, an industry marked by high intangible asset intensity and regulatory sensitivity. Using panel data from eight publicly listed pharmaceutical companies on the Indonesia Stock Exchange (IDX) for the 2019–2023 period, the research employs a Random Effect Model to assess the impact of tax ratio, firm size, intangible assets, and tunneling incentive on transfer pricing decisions. The findings reveal that the tax ratio is the only variable that has a statistically significant and positive impact on transfer pricing, confirming the theory that higher tax burdens encourage firms to shift profits through intra-group transactions. In contrast, firm size, intangible assets, and tunneling incentives exhibit no significant effects, indicating that structural characteristics alone may not fully explain transfer pricing behavior in emerging markets. This study enriches the discourse on agency theory and positive accounting theory by highlighting how managerial decisions are primarily influenced by fiscal constraints rather than firm complexity or ownership motives. It challenges widely held assumptions that larger firms or those with higher intangible assets are more prone to transfer pricing, especially in contexts with growing regulatory enforcement such as Indonesia. The results underscore the importance of risk-based tax auditing strategies that target firms with high tax exposure, rather than relying solely on observable characteristics like size or asset structure.